PENGARUH KELEKATAN AMAN (SECURE ATTACHMENT) TERHADAP KEMANDIRIAN ANAK USIA DINI DI TK MUTIARA KOTA PEKANBARU - Yuni, Putri Ismi; N, Zulkifli; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aims is know the effect of secure attachment to theindependence of young children in TK Pekanbaru City. The population in this study was32 early childhood. The sampling technique is saturated by means of nonprobabilitysampling. Survey method with correlation techniques to see the secure attachmentvariable with the independence variable. Observation data collection techniques usingobservation sheets. The data analysis technique uses correlation test with SPSS forWindows ver. 23. The results of the study show that the safety of early childhood is inthe sufficient category with a value of 68.8% and the independence of early childhood is in the sufficient category with a value of 62.5%. Based on the hypothesis test obtained there is a positive relationship and significance between secure attachment with the independence of young children in kindergarten Mutiara Kota Pekanbaru. This is known from the value of the correlation coefficient of rxy = 0.678 and the significance level of 0.000 <0.05. The level of influence of secure attachment with independence is included in the strong category with the resulting coefficient of determination of 45.9%, meaning secure attachment gives an effect of 45.9% of independence.Key Words : Secure Attachment, Independence,Children.